The Violence in Laws: The Use of Force and the Criminalization of Socio-Environmental protests in Peru - Saldaña Cuba, José (2017)
This paper does a profound description of the legal framework and its recent modifications related to the State’s use of force in socio-environmental conflicts. This analysis emphasizes in law’s violent nature as a theoretic approach that intends on showing the way that the legal system, instead of defending rights, violates them. The methodology is dogmatic when analyzing law and other legal documents, and interdisciplinary when comparing laws with evidence gathered in interviews, participant observation, documents and databases. The objective its to characterize critically the complex legal framework that articulates the politics that leads to the criminalization of social protests against extractive industries in Peru.